Book Review Sovereignty and the Sea: How Indonesia Became An Archipelagic State - Soepandji, Kris Wijoyo (Indonesia Law Review, 2018)
The book, which is published by the National University of Singapore Press, is written by two professors, John G. Butcher and R. E. Elson who are based in Australia. The writers explained on how Indonesia managed to earn the place as the greatest archipelagic state in the world, as gaining international recognition for its claim when the United Nations Convention on the Law of the Sea formally recognized the existence of a new category of states known as “archipelagic states” which had given these states sovereignty over their “archipelagic waters”, in the year of 1982. The book which has very strong subject on Indonesian and International Law is written by two professors which have no law background, put the important point on how a small group of Indonesians diplomat gave their persistence effort and finally give tremendous effect on how International Law of the Sea is currently conducted.